Implementasi Pelayanan Prima Sebagai Upaya Meningkatkan Marketing Sekolah - Puspitasari, Fantika Febry (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
Education is a public service institution that aims to educate the nation. In achieving this goal, SDIT Taqiyya Rosyida is committed to dedicate excellent services to achieve the quality of education. The purpose of this research is to know how to implement excellent services as an effort to improve the marketing of schools in SDIT Taqiyya Rosyida. This research uses qualitative methods of descriptive. Data is collected through observation, interviews, and documentation. Research subjects are principals and research informers include teachers, students, employees, and parents. The results of this research are the implementation of excellent services in the form of: 1) Training of Excellence Services, 2) creating friendly communication, 3) animate a family atmosphere, 4) provide quality facilities, where the implementation of excellent services was able to make SDIT Taqiyya Rosyida reached the acceptance of 112 students divided into 4 study groups, in the fifth year.